(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-168-177 The article shows how the newspapers of the municipal districts of the Novosibirsk region are represented in social networks. The relevance of the stated topic is due to the fact that expanding interaction with social networks is one of the main features and trends in the development of regional and local press markets in Russia. The novelty is determined by the lack of published scientific articles concerning the current state of affairs in such a large region as the Novosibirsk region, as well as the empirical nature of the work carried out, which made it possible to trace the current state of this segment of the media sphere. The article presents the results of the analysis of audience indicators of public newspapers and monitoring of their content both in traditional social networks, such as VKontakte and Odnoklassniki, and in the relatively new Telegram, YouTube or Yandex.Zen. It is shown that all newspapers of this type have their own pages, on average they have 1.5–3 thousand subscribers on VKontakte and Odnoklassniki. The median number of posts per week is 22.5 posts for VKontakte and 20.8 for Odnoklassniki. At the same time, new platforms, such as Telegram, are just beginning to attract the interest of editorial offices — nine newspapers launched their tg channels in the spring of 2022, but the number of subscribers there is not yet large. Key words: newspapers, local newspapers, district newspaper, rural district, integration into social networks, media platforms, page in social networks.